2010
DOI: 10.1103/physrevlett.105.253901
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Airy Light Bullets in the Linear and Nonlinear Regimes

Abstract: We demonstrate the realization of intense Airy-Airy-Airy (Airy(3)) light bullets by combining a spatial Airy beam with an Airy pulse in time. The Airy(3) light bullets belong to a family of linear spatiotemporal wave packets that do not require any specific tuning of the material optical properties for their formation and withstand both diffraction and dispersion during their propagation. We show that the Airy(3) light bullets are robust up to the high intensity regime, since they are capable of healing the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
214
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 414 publications
(217 citation statements)
references
References 21 publications
2
214
0
1
Order By: Relevance
“…15 The Airy modes also exist in the form of non-diffracting surface plasmon, [16][17][18] self-accelerating acoustics, 19 electron beams, 20 as well as spatiotemporal non-spreading light bullets. 21 In the present work, an ultra-long needle focus was experimentally generated through the creation of a rectangularly symmetric Airy beam (SAB) 22,23 with binary spectral amplitude modulation. The SAB first autofocuses and appears with a single central lobe, then the lobe splits into four Airy main lobes, and it looks like a combination of four Airy beams with an outward acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…15 The Airy modes also exist in the form of non-diffracting surface plasmon, [16][17][18] self-accelerating acoustics, 19 electron beams, 20 as well as spatiotemporal non-spreading light bullets. 21 In the present work, an ultra-long needle focus was experimentally generated through the creation of a rectangularly symmetric Airy beam (SAB) 22,23 with binary spectral amplitude modulation. The SAB first autofocuses and appears with a single central lobe, then the lobe splits into four Airy main lobes, and it looks like a combination of four Airy beams with an outward acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Airy beam proves very resilient to perturbations, as it is able to linearly reconstruct (self-heal) itself 5 . Further research activity on Airy beams in the non-linear regime has revealed stationary non-linear 1D solutions 6 , (3 þ 1)D non-linear light bullets 7 , solitons in self-defocusing media 8 and other newly observed spatial mechanisms 9,10 . Recently, the Airy wavepacket concept has also been demonstrated for electron packets 11 .…”
mentioning
confidence: 99%
“…18 Such third order phase control leads to temporal pulse shapes that are termed Airy pulses. 19 Furthermore, it was recently shown that the volume of laser-excitation in bulk water can be controlled by such pulse shapes. 20 By using positive third order dispersion laser pulses, the area of excitation can be reduced by nearly a factor of two while the depth of the excitation reached much deeper inside the bulk water sample.…”
mentioning
confidence: 99%